Asian elephant interferons alpha and beta and their anti-herpes viral activity - Haycock, Jonathan; Maehr, Tanja; Dastjerdi, Akbar; Steinbach, Falko (Frontiers in Immunology, 2025)
The type I interferons (IFNs) are a group of key cytokines of the vertebrate innate immune system that induce an antiviral state in uninfected cells. Experimental in-vitro and in-vivo data have proven the fundamental role these cytokines possess in the protective response to a wide variety of pathogens, including herpesviruses. In a clinical setting, IFNs have been an important treatment in humans for several decades and increasing evidence demonstrates their potential in controlling viral haemorrhagic fevers when administered early in disease. In juvenile Asian elephants, elephant endotheliotropic herpesvirus haemorrhagic disease (EEHV-HD) often proves fatal when an effective adaptive immune response cannot be mounted in time, suggesting that an enhancement of the innate immune response could provide protection. This study sequenced six members of the Asian elephant type I IFNs, most closely related to sequences from the African elephant and Florida manatee. Subsequently, recombinant Asian elephant IFNα and IFNβ proteins were expressed and assessed for bioactivity in-vitro, relative to recombinant human IFNs, using a novel infection model incorporating primary Asian elephant fibroblasts and bovine alphaherpesvirus 1 (BoHV-1) as a surrogate for EEHV. In a dose-dependent manner, both Asian elephant IFNs and human IFNα2a protected cells from BoHV-1 infection in this proof-of-concept study, even if applied up to 24 hours post-infection in-vitro.